2022
DOI: 10.3390/ani12202813
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Commercial Enzyme-Linked Immunosorbent Assay (ELISA) with the Modified Agglutination Test (MAT) for the Detection of Antibodies against Toxoplasma gondii in a Cohort of Hunting Dogs

Abstract: Toxoplasmosis is a zoonotic disease, caused by the protozoan Toxoplasma gondii, affecting most warm-blooded animals. Assessing the seroprevalence of T. gondii in different animal species gives a good estimate of the global circulation of the parasite and the risk for human infections. However, the seroprevalence of T. gondii in dogs is not studied as much as other species, despite their close contact with wildlife and humans in rural or urban environments and evidence that dogs can also be a potential source f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Modified agglutination test (MAT) and ELISA are highly specific methods widely used for the detection of antibodies to T. gondii, and applicable for serological diagnosis of infection as well as in epidemiological studies. Several authors compared ELISA and agglutination test for the detection of T. gondii and declared lower specificity and sensitivity of MAT than that of ELISA [34,35]. Moreover, the agglutination test can detect only IgG antibodies, while goat Anti-Mouse Polyvalent Immunoglobulins (G, A, M) used for ELISA in the presented study, is capable to detect three classes of antibodies, IgG, IgM and IgA.…”
Section: Discussionmentioning
confidence: 91%
“…Modified agglutination test (MAT) and ELISA are highly specific methods widely used for the detection of antibodies to T. gondii, and applicable for serological diagnosis of infection as well as in epidemiological studies. Several authors compared ELISA and agglutination test for the detection of T. gondii and declared lower specificity and sensitivity of MAT than that of ELISA [34,35]. Moreover, the agglutination test can detect only IgG antibodies, while goat Anti-Mouse Polyvalent Immunoglobulins (G, A, M) used for ELISA in the presented study, is capable to detect three classes of antibodies, IgG, IgM and IgA.…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, Caramalac et al (2021) observed seroprevalence rates of 35.9% for T. gondii and 15.4% for N. caninum in Mato Grosso do Sul. Furthermore, the seroprevalence of antibodies against both parasites in hunting dogs in this study exceeded rates reported in studies from other regions of the world: 19.6% for T. gondii using the latex agglutination test in Taiwan ( Fan et al, 1998 ); 15% for N. caninum and 24% for T. gondii using IFAT in Spain ( Machačová et al, 2016 ); 52.8% for T. gondii using the modified agglutination test in Spain and Africa ( Cano-Terriza et al, 2016 ); and a mean of 36.8% for T. gondii using ELISA and modified agglutination test in Algeria ( Bellatreche et al, 2022 ).…”
Section: Discussionmentioning
confidence: 98%
“…To find antibodies against Toxoplasma gondii in a cohort of hunting dogs, researchers used an ELISA with the modified agglutination test (MAT) (Bellatreche et al 2022) Radioimmunoassay An antigen or antibody that has been radiolabeled binds to it, such as when it is connected to the solid phase.…”
Section: Specimen Preparation For Inoculationmentioning
confidence: 99%